9x+14=3(3x+5)

Simple and best practice solution for 9x+14=3(3x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+14=3(3x+5) equation:


Simplifying
9x + 14 = 3(3x + 5)

Reorder the terms:
14 + 9x = 3(3x + 5)

Reorder the terms:
14 + 9x = 3(5 + 3x)
14 + 9x = (5 * 3 + 3x * 3)
14 + 9x = (15 + 9x)

Add '-9x' to each side of the equation.
14 + 9x + -9x = 15 + 9x + -9x

Combine like terms: 9x + -9x = 0
14 + 0 = 15 + 9x + -9x
14 = 15 + 9x + -9x

Combine like terms: 9x + -9x = 0
14 = 15 + 0
14 = 15

Solving
14 = 15

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 6v^2-42v=0 | | 3a+7b=82 | | 3*42/6 | | -76=2(-8+5v) | | (x-4)/(x^2+2) | | 8x+8=7x+13 | | -3n-6=0 | | 4x-5+7=10 | | X=(4-1/3)/(1/3) | | -8r-8r=0 | | F=1/3(41)+1/3 | | F=1/3(12)+1/3 | | 4x-20=-6x | | (6k-7)(8k+5)= | | 3.333+y=6 | | 2x+37=5x+4 | | (2x-3)(2x-3)(2x-3)=0 | | 3x/-8=-3 | | 5=4x+8 | | 2f(5f-2)-10(f^2-3f+6)=-8f(f+4)+4(2f^2-7f) | | 54/9-32/9 | | 16x^4-9x^2= | | 5x=y+3/2 | | 16c^2+18+5=0 | | 4+3(X-9)=12 | | (6t-7)(t+2)=-10 | | 1440=x(x-18) | | 16x^4-9x^4= | | 2Q+3T=44 | | 0.3(2-3r)=2.1r+6 | | 15/5/20/3+7 | | (-2a^3/b)^5 |

Equations solver categories